Development of Whole and Ground Seed Near‐Infrared Spectroscopy Calibrations for Oil, Protein, Moisture, and Fatty Acids in Salvia hispanica. (15th October 2019) - Serson, William; Armstrong, Paul; Maghirang, Elizabeth; AL‐Bakri, Ahmed; Phillips, Timothy; AL‐Amery, Maythem; Su, Kai; Hildebrand, David
Abstract: Chia ( Salvia hispanica ) is an ancient crop that has experienced an agricultural resurgence in recent decades owing to the high omega 3 fatty acid (ω‐3) content of the seeds and good production potential. Analysis of 563 lots of chia grown in Kentucky and 10 lots from Arizona, Australia, Mexico, and Peru was performed. All of these lots were assessed for fatty acid, oil, and protein content, while a subset of 120 samples were assessed for amino acids, fiber, minerals, and trace elements. The mean oil content was 31.3%, ranging from 21.4% to 35.3%. The protein content averaged 22.8%, ranging from 18.2% to 28.2%, and the ω‐3 FA α‐linolenic acid (ALA) averaged 61.3%, ranging from 33.9% to 69.9%. Using these seed lots, nondestructive near‐infrared spectroscopy (NIRS) calibrations were developed for whole and ground seed oil, protein, moisture, and the six major fatty acids. The R 2 and SE of cross‐validation (SECV) values for oil were 0.78 and 0.95, respectively, while those for protein were 0.75 and 1.05, respectively. The NIRS calibrations for fatty acid had R 2 and SECV greater than 0.6 and less than 10% of actual values for all major fatty acids, respectively. An R 2 of 0.99 was established for moisture content of whole seeds within the range of 3–10% moisture content. The precision and accuracy of these calibrations is adequate for use by breeders, growers, and food quality experts to quantitatively assess these major constituents without the need for costly and time‐consuming chemical analysis.